Pemenuhan Hak Atas Kesehatan Bagi Kelompok Rentan di Kota Ternate - Salha Marasaoly; Sri Indriyani Umra (JURNAL USM LAW REVIEW, 2026)
This study examines the fulfillment of the right to health for vulnerable groups in Ternate City and evaluates the role of the local government in ensuring equitable access to health services. Vulnerable groups—including children, older persons, persons with disabilities, and low-income communities—frequently encounter structural, geographical, and administrative barriers that limit their access to adequate healthcare. This research employs a normative legal method combined with an empirical juridical approach through statutory analysis, legal doctrines, field observations, and interviews. The analysis refers to the 1945 Constitution of the Republic of Indonesia, Law No. 17 of 2023 on Health, Law No. 39 of 1999 on Human Rights, Law No. 23 of 2014 on Local Government, and international human rights instruments, particularly the UDHR and ICESCR. The findings indicate that although various programs, such as primary healthcare services, the National Health Insurance scheme, and mobile and sea ambulance services, have improved service availability, significant challenges persist in terms of accessibility, inclusiveness, service quality, and responsiveness to the specific needs of vulnerable groups. The study highlights the need for affirmative and rights-based policies that integrate the principles of availability, accessibility, acceptability, and quality (AAAQ). This research contributes to strengthening local health governance by providing context-based policy recommendations for inclusive and equitable health services in archipelagic regions. Penelitian ini menganalisis pemenuhan hak atas kesehatan bagi kelompok rentan di Kota Ternate serta mengevaluasi peran pemerintah daerah dalam menjamin akses layanan kesehatan yang setara dan berkeadilan. Kelompok rentan—meliputi anak-anak, lanjut usia, penyandang disabilitas, dan masyarakat miskin—masih menghadapi hambatan struktural, geografis, dan administratif yang membatasi akses terhadap pelayanan kesehatan yang layak. Penelitian menggunakan metode hukum normatif yang dipadukan dengan pendekatan yuridis empiris melalui analisis peraturan perundang-undangan, doktrin hukum, observasi lapangan, dan wawancara. Analisis didasarkan pada UUD NRI 1945, Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan, Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia, Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah, serta instrumen internasional UDHR dan ICESCR. Hasil penelitian menunjukkan bahwa berbagai program kesehatan seperti penguatan layanan primer, Jaminan Kesehatan Nasional, serta ambulans darat dan laut telah meningkatkan ketersediaan layanan, namun masih terdapat kendala pada aspek keterjangkauan, inklusivitas, kualitas, dan responsivitas terhadap kebutuhan spesifik kelompok rentan. Penelitian ini menegaskan pentingnya kebijakan afirmatif berbasis hak dengan menerapkan prinsip ketersediaan, keterjangkauan, keberterimaan, dan kualitas (AAAQ). Temuan ini berkontribusi pada penguatan tata kelola kesehatan daerah melalui rekomendasi kebijakan yang lebih inklusif dan adaptif bagi wilayah kepulauan.